THE USE OF AMNIOTIC MEMBRANE FOR WOUND HEALING IN BURN INJURIES - Prawoto, Almas Nur; Ishandono Dachlan (Universitas Airlangga, 2022)
HIGHLIGHTS: 1. An organic bandage that can be helpful in the treatment of burn wounds is amniotic membrane. 2. The mechanisms of amniotic membrane for the treatment of burns and wounds should be investigated and understood in more detail. ABSTRACT: Introduction: Burn injuries are associated with significant mortality and morbidity around theworld. The care of burn wounds requires a great amount of medical resources, therefore it is important to find a wound dressing that accelerates wound healing and is readily available. Methods: Literature search from online databases using relevant keywords about the usage of amniotic membranes in burn patients. Results: Research has shown that it contains antimicrobial properties that could be of great benefit in burn patients and is compatible to use in developing countries because it is readily available, easy to obtain and sterilize, able to cover wounds of large size, protects the wound from excessive water and electrolyte loss, reduces pain intensity, requires fewer dressing changes and is also more cost effective than conventional dressings. Conclusion: Amniotic membrane is a biological dressing that can be useful in the treatment of burn wounds. Further research should be conducted to investigate and understand the mechanisms of amniotic membrane for burn and wound care.